1987
DOI: 10.1515/text.1.1987.7.4.313
|View full text |Cite
|
Sign up to set email alerts
|

The unequal distribution of interactional space: Dominance and control in courtroom interaction

Abstract: This paper deals with the interaction between legal Professionals and defendants in criminal court trials, The data corpus consists of40 trials recorded in aSwedish district court, all featuring minor economic offences. Analyses focus particularly upon the ways in which the discourse space is shared. The interplay between the various types ofdirecting and controlling moves adopted by fudges and lawyers, and defendants' attempts to voice their points ofview is accounted for. The quantitative pari of the study m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 10 publications
3
23
0
4
Order By: Relevance
“…Open single-unit questions sometimes occur as opening questions in courtroom interviews. Nevertheless, Adelswärd et al (1987) found that legal professionals often preferred topic-openers with multi-unit designs ending in closed-ended questions (see extract [1] lines [1][2][3][4][5]. Interestingly, this happened more often with more serious offenders ('recidivists') than with first-time defendants; it seems that the professionals used the constraining 'question cascades' (i.e., 'different versions of what is ostensibly the same question' [Clayman and Heritage 2002: 757]) when they were particularly concerned about controlling and steering the interview more strongly.…”
Section: A Tcu Within a Muqt Is Prototypicallymentioning
confidence: 99%
“…Open single-unit questions sometimes occur as opening questions in courtroom interviews. Nevertheless, Adelswärd et al (1987) found that legal professionals often preferred topic-openers with multi-unit designs ending in closed-ended questions (see extract [1] lines [1][2][3][4][5]. Interestingly, this happened more often with more serious offenders ('recidivists') than with first-time defendants; it seems that the professionals used the constraining 'question cascades' (i.e., 'different versions of what is ostensibly the same question' [Clayman and Heritage 2002: 757]) when they were particularly concerned about controlling and steering the interview more strongly.…”
Section: A Tcu Within a Muqt Is Prototypicallymentioning
confidence: 99%
“…During the observer training, several indicators of dominance were discussed: interruption, questioning, topic control, formulation and amount of talk (e.g., Adelswärd et al, 1987;Duff, 1986;Kollock, Blumstein, & Schwartz, 1985;Linell, 1990;Roger & Schumacher, 1983;Ten Have, 1991). Observers evaluated this relative dominance between dental and dental hygiene students within a mixed profession group using an ordinal scale (to score the perceived image related to dominance): −1 = dental dominance, 0 = no dominance, +1 = dental hygiene dominance.…”
Section: Observation Item 2 Relative Dominancementioning
confidence: 99%
“…Reformulations can be hence described as ''combative'' in the witness examination since they create a linguistic conflict between the legal professional and the witness. Indeed, as [1] explain, the lawyer proposes a version of the evidence only picking up certain elements of the witness' narrative chosen to be favourable to his/her line of argument and changing those conflictual. The task of the legal professionals is to create a credible narrative to be submitted to the jury in order to obtain a positive verdict for their clients.…”
Section: Introductionmentioning
confidence: 99%